Checklist of the Mediterranean Fishes of Israel - Golani, Daniel (Zootaxa, 2005)
A checklist of the Mediterranean marine ichthyofauna of Israel is presented. A total of 402 species belonging to 130 families, 33 orders and 3 classes are listed. The checklist includes all synonyms for each species and citations of all known publications, listed in chronological order, concerning occurrence in Israeli waters of each species. Citations are coded to indicate the focus of each publication.